AN ANALYSIS OF ACCELERATED CLASSROOM IN INDONESIA - Siti Safura (Jurnal Dedikasi Pendidikan, 2017)
Accelerated classroom has become the meaningful program in the school that given for the special students.  Since the use of same curriculum that has been modified between acceleration class and normal class becomes a debate. This paper presents an analysis of the differences in achievement between acceleration students and regular students. Also, it gives a description of prospects and problems of accelerated classroom in Indonesia. The account of the difference between regular students and non-regular students is exposed from three paradigm; psychology, curriculum, and economic. The conversation provides pro and con regarding to the existence of the acceleration class. The reflection about the gifted students who have high ability, Indonesia should hold acceleration class to meet their needs.